Analisis Total Suspended Solid (TSS) Perairan Danau Toba di Kecamatan Girsang Sipangan Bolon, Sumatera Utara - Panjaitan, Angelina Juniarta; Ulinuha, Devi; Ernawati, Ni Made (Current Trends in Aquatic Science; Vol 6 No 2 (2023), 2023)
Lake Toba, one of the largest lakes in Indonesia, is located in the province of North Sumatera, which has a significant tourism sector. Increased human activity can place the aquatic ecosystem of Lake Toba under great ecological pressure. Total Suspended Solids (TSS) are an important water quality indicator. Various human activities are carried out on Lake Toba, including fish farming in floating net cages (KJA), tourism, and water transportation. This activity produces organic and inorganic substances that have the potential to reduce water quality. Based on the research results, the concentration of total suspended solids (TSS) at five sampling locations exceeded class II water quality standards. The TSS concentration has different variations from the other 4 water sampling points because the 4 water sampling points are not passed by shipping lanes. The large TSS values at the 5 water sampling points can be caused by domestic waste generated from port activities, water transportation, tourism activities, hotels, and offices.